One Goal, Many Roads: Investigating Individual Differences in L2 Willingness to Communicate Among University Freshmen - Purba, Hilarius Raditya Priambada; Togatorop, Sarah Ayuandri; Pratiwi, Theodesia Lady; Prasodjo, Pandu; Zaki , Leil Badrah (Universitas Pendidikan Mandalika, 2025)
This study examines the influence of Individual Differences (ID) on freshmen’s L2 Willingness to Communicate (WTC) in English as a Foreign Language (EFL) learning context. The study you provided explores the role of ID in determining WTC in EFL learners, emphasizing how these differences affect language proficiency and communicative competence. The main gap addressed in this study is the lack of focus on personalized language learning strategies that take into account individual differences in WTC and proficiency among EFL learners The study employs a qualitative method, data were collected through questionnaires for selective the participants by using the purposive sampling and semi-structured interviews were driven with the selected participants. The result has showed that factors such as self-confidence, motivation, language anxiety, classroom atmosphere, and peer support significantly shaped students’ WTC. Students with positive self-perception and supportive environment were likely have the L2 willingness to communicate in English. On the other hand, anxiety, fear of making mistakes, and unsupportive settings hindered participation. An effective strategy identified was personal preparation that gradually facilitated the students to the speaking opportunities and fostering a supportive and non-judgmental classroom environment. The research highlights the importance of considering individual learning characteristics in designing communicative language learning strategies to improve students speaking confidence and language acquisition outcomes. The further implications of teaching and learning process should be more open to facilitate student’s IDs and to be more personalized.